2020
DOI: 10.1007/s40831-020-00294-3
|View full text |Cite
|
Sign up to set email alerts
|

Ammoniacal Solvoleaching of Copper from High-Grade Chrysocolla

Abstract: The copper silicate ore chrysocolla forms a large potential copper resource, which has not yet been fully exploited, due to difficulties associated with its beneficiation by flotation and metallurgical processing. Direct acid leaching of chrysocolla causes silica gel formation. Therefore, in this work, the feasibility of solvometallurgical methods to leach copper from high-grade chrysocolla while avoiding issues with silica gel formation was assessed. Ammoniacal solvoleaching was performed with a solvent compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…While roasting increased the leachability, less than 70% of the copper was leached via conventional ammoniacal leaching. To increase the efficiency of the process, a simultaneous leaching and SX were investigated. , In this process, the solid (S) is allowed to contact with two immiscible liquid phases, that is, the aqueous lixiviant phase (A) and the organic extractant phase (O). The solid is leached by the aqueous phase, but the leached metals are immediately extracted to the organic phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While roasting increased the leachability, less than 70% of the copper was leached via conventional ammoniacal leaching. To increase the efficiency of the process, a simultaneous leaching and SX were investigated. , In this process, the solid (S) is allowed to contact with two immiscible liquid phases, that is, the aqueous lixiviant phase (A) and the organic extractant phase (O). The solid is leached by the aqueous phase, but the leached metals are immediately extracted to the organic phase.…”
Section: Resultsmentioning
confidence: 99%
“…To increase the efficiency of the process, a simultaneous leaching and solvent extraction (SX) was investigated. 35,36 In this process, the solid (S) is contacted with two immiscible liquid phases, i.e. the aqueous lixiviant phase (A) and the organic extractant phase (O).…”
Section: Ammoniacal Leachingmentioning
confidence: 99%
“…22 Leaching of low-grade complex copper ore in an ammonia−ammonium chloride system readily extracted 63−100% of the malachite phases but only 2−37% of the chrysocolla phases. 24 A solvometallurgical leaching system consisting of a chelating extractant, an aliphatic diluent, and aqueous ammonia obtained the best result of 75% copper extraction yield from high-grade chrysocolla ore. 9 An unwanted stable emulsion was formed at the interface between the organic and aqueous phase during the subsequent stripping process, which then required the addition of a modifier. Solvometallurgy is a relatively new approach in the extractive metallurgy that may offer advantages over hydrometallurgical processing, for example, minimizing problems with silica gel and obtaining a higher leaching selectivity compared to acid leaching.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, Gijsemans et al used the chelating extractant LIX 984 N (equivolume mixture of 2-hydroxy-5-nonylacetophenone oxime and 5-dodecylsalicylaldoxime) as lixiviant to solvoleach copper from chrysocolla, after which the copper-loaded organic phase was directly stripped by a mineral acid. 28 Using non-aqueous lixiviants during solvoleaching could avoid the formation of toxic and/or dangerous gasses compared to leaching with conventional mineral acids, which is a potential benefit. 26 It has been demonstrated that process intensification by integration of unit operations not only reduces the operating costs but it also improves the safety, greenness and energy efficiency of processes.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] For example, in the process of Gijsemans et al, the number of solvent extraction steps was reduced. 28 If their process would be up-scaled in countercurrent mode, it would require fewer mixer-settler units and smaller volumes of chemicals, and would produce less aqueous waste. Furthermore, several recent studies on LIB recycling have shown that the aluminium and copper current collectors can also reduce cobalt(III) during the leaching of cathode material, which could avoid pre-separation steps and in turn reduce energy costs.…”
Section: Introductionmentioning
confidence: 99%